A performance optimization algorithm for controller reconfiguration in fault tolerant distributed model predictive control - Zakharov, Alexey; Zattoni, Elena; Miao Yu; Jamsa-Jounela, Sirkka-Liisa (2015 IEEE International Conference on Automation Science and Engineering (CASE), 2015)
This paper presents a performance optimization algorithm for controller reconfiguration in fault tolerant distributed model predictive control for large-scale systems. After the fault has been detected and diagnosed, several controller reconfigurations are proposed as candidate corrective actions for the fault compensation. The solution of a set of constrained DMPC optimization problems with different actuator and setpoint reconfigurations is derived by means of an original approach that exploits the information on the active constraints in the non-faulty subsystems, so as to split the global optimization problem into two optimization subproblems, which enables the on-line computation burden to be greatly reduced. Subsequently, the performances of different candidate controller reconfigurations are compared, and the better performing one is selected and then implemented to compensate the fault effects. Simulation results on a benzene alkylation process have demonstrated the efficacy of the proposed performance optimization algorithm in the fault tolerant distributed model predictive control.